Rapid Purification and Characterization of Mutant Origin Recognition Complexes in Saccharomyces cerevisiae - Kawakami, Hironori; Ohashi, Eiji; Tsurimoto, Toshiki; Katayama, Tsutomu (Frontiers in Microbiology, 2016)
Purification of the origin recognition complex (ORC) from wild-type budding yeast cells more than two decades ago opened up doors to analyze the initiation of eukaryotic chromosomal DNA replication biochemically. Although revised methods to purify ORC from overproducing cells were reported later, purification of mutant proteins using these systems still depends on time-consuming processes including genetic manipulation to construct and amplify mutant baculoviruses or yeast strains as well as several canonical protein fractionations. Here, we present a streamlined method to construct mutant overproducers, followed by purification of mutant ORCs. Use of mammalian cells co-transfected with conveniently mutagenized plasmids bearing a His tag excludes many of the construction and fractionation steps. Transfection is highly efficient. All the six subunits of ORC are overexpressed at a considerable level and isolated as a functional heterohexameric complex. Furthermore, use of mammalian cells prevents contamination of wild-type ORC from yeast cells. The method is applicable to wild-type and at least three mutant ORCs, and the resultant purified complexes show expected biochemical activities. The rapid acquisition of mutant ORCs using this system will boost systematic biochemical dissection of ORC and can be even applied to the purification of protein complexes other than ORC.